Moving Closer to Cell Therapies for PD - Nierengarten, Mary Beth (MD Conference Express, 2014)
Current treatment for Parkinson's disease (PD) using dopamine agents to replace the loss of dopaminergic neurons has helped to ameliorate some of the motor features of the disease in its early stages. This significant response to dopamine agents has provided the rationale for testing cell-based therapies for replacement of lost dopamine neurons in the hope of altering the natural history of PD by slowing the progression of signs and symptoms. This article discusses the current research on cell transplantation as therapy for PD and discussed the prospects for using stem-cell therapy for clinical transplantation